Long‐term stream hydrology and meteorology of a Polar Desert, the McMurdo Dry Valleys, Antarctica. Issue 6 (20th June 2022) - Gooseff, Michael N.; McKnight, Diane M.; Doran, Peter T.; Fountain, Andrew
Abstract: The McMurdo Dry Valleys (MDVs; 77.50°S, 162.25°E) make up the largest ice‐free region of Antarctica at 3500 km 2 . Their position near the coast of the Ross Sea provides for a milder climate than much of the rest of the continent. Alpine and piedmont glaciers in the MDVs melt during the austral summer providing water to down gradient streams and terminal lakes on valley floors. There are currently 14 meteorological stations and 17 stream gauges operating across the MDVs, some with continuous records that go back to 1969. This relatively high density of monitoring stations reflects the fact that glaciers of different sizes and elevation ranges are the main source of water to streams. Thus, each glacier represents a different watershed. The bulk of these records start in the late 1980s/early 1990s. These data collection activities directly support research endeavours of the McMurdo Dry Valleys Long Term Ecological Research project, as well as a host of other science groups working in the MDVs. As such, both real time data and archived data from these sites is available through the online database interface of the project (http://mcmlter.org ). Abstract : Streamflow and meteorology in the polar desert landscape of the McMurdo Dry Valleys, Antarctica have been routinely measured since 1969. These long‐term data sets provide insight into fundamental hydrological processes and the earth system's response to change.